2004
DOI: 10.1177/0192512104038165
|View full text |Cite
|
Sign up to set email alerts
|

Christian Conservatives Go to Court:Religion and Legal Mobilization in the united States and Canada

Abstract: The American exceptionalism thesis holds that American political culture produces an unusually litigious society. The US Christian right has participated in litigation, especially in constitutional rights cases dealing with issues such as religious schools and abortion. However, since 1982 Canada has had a constitutional Charter of Rights and an increasingly active Christian right of its own. We compare data on Christian right involvement in education, abortion, and "right to die" (euthanasia, assisted suicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…As in the U.S., however, Canadian religious groups use litigation to promote their policy agendas. Hoover and den Dulk (2004) found that the Religious Right litigated thirty-one right-tolife cases before the U.S. Supreme Court between 1975 and 2001; the same was true in thirteen such cases before the Canadian Supreme Court between 1984 and 2001.…”
Section: Religionmentioning
confidence: 83%
“…As in the U.S., however, Canadian religious groups use litigation to promote their policy agendas. Hoover and den Dulk (2004) found that the Religious Right litigated thirty-one right-tolife cases before the U.S. Supreme Court between 1975 and 2001; the same was true in thirteen such cases before the Canadian Supreme Court between 1984 and 2001.…”
Section: Religionmentioning
confidence: 83%
“…For much of the last 50 years, moreover, American courts embraced an even more relaxed approach to standing on church‐state matters, which facilitated a flood of religious litigation (Green ). The relaxation of standing rules has also encouraged religious litigation in several other jurisdictions, including Canada (Hoover and den Dulk ) and the European Union. Even today, the ECtHR's relatively permissive standing requirements continue to make it a readier target than the CJEU, which has stricter standing rules (Fokas , ).…”
Section: Courts As Institutions: Internal Variation and The Possibilimentioning
confidence: 99%
“…This issue is also highly relevant to studies of religion and politics as it is one of the most salient and frequent issues in which religious groups are involved, taking action before the Supreme Court, with members of Congress, within presidential campaigns, and in local politics (Ivers 1992; Wilcox and Larson 2006). Religious groups have been effective in setting the church‐state agenda and in achieving victories on church‐state issues in Congress and before the Court (Greenawalt 1994; Hacker 2005; Hoover and Dulk 2004). Recently, conservative religious groups have been influential in counteracting the strict‐separation interpretation of the First Amendment (Epstein 1985; Hacker 2005; Teles 2008).…”
Section: Case Study: Baptist Groups and Church‐state Politicsmentioning
confidence: 99%